2012
DOI: 10.3109/00365521.2012.743585
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of symptom duration and fecal bacteriotherapy inClostridium difficileinfection-pooled data analysis and a systematic review

Abstract: FMT is a safe and effective treatment option for CDI. Shorter duration of symptoms (< 60 days) before administering FMT is associated with treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…These bacteria are influenced by one another as well as by the host. This point has been well documented in several model systems, which demonstrate that bacteria use small molecules such as bile acids to communicate and survive (Sofi et al, 2013). Bile acids in the cecum are deconjugated by microbial-derived bile salt hydrolases into primary bile acids such as cholate (Ridlon et al, 2006), which can stimulate the germination of C. difficile spores (Francis et al, 2013).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These bacteria are influenced by one another as well as by the host. This point has been well documented in several model systems, which demonstrate that bacteria use small molecules such as bile acids to communicate and survive (Sofi et al, 2013). Bile acids in the cecum are deconjugated by microbial-derived bile salt hydrolases into primary bile acids such as cholate (Ridlon et al, 2006), which can stimulate the germination of C. difficile spores (Francis et al, 2013).…”
mentioning
confidence: 95%
“…Consequently, some individuals become refractory to antibiotics and have recurrent CDI. On a brighter note, the use of fecal microbiota transplants (FMTs) as a therapy has been very effective in the treatment of relapsing CDI (Sofi et al, 2013). Yet a major gap exists in our understanding of the interaction between the host-microbe relationship and the microbial factors that confer resistance and susceptibility to CDI.…”
mentioning
confidence: 99%
“…It is because these individuals and the recipients have similar intestinal microenvironment, which may produce a satisfactory effect of transplantation. While a meta‐analysis showed no significant differences in the effectiveness between related and unrelated donors ( P = 0.46), It has been suggested that male donors are preferred to female donors because feces of the latter might carry high‐risk factors of IBS . Another research indicated gender differences between donors and recipients had little effect on disease remission, but there owned insufficient evidence .…”
Section: The Mechanism and Clinical Use Of Fmtmentioning
confidence: 98%
“…FMT is one therapy that has risen in prominence since the early 2010s, due primarily to its startlingly high efficacy (over 90% success rate reported in some studies (125, 126)). FMT, however, is not a new idea.…”
Section: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%